Obstetric and gynecological history and arterial stiffness in women of different age groups - Olga S. Ivanova; Elena Yu. Maychuk; Svetlana V. Yureneva; Irina V. Voevodina (IP Berlin A.V., 2022)
Aim. To study the correlation between the features of obstetric and gynecological anamnesis with indicators of arterial stiffness in women of different age groups to assess additional risk factors for the development of cardiovascular diseases. Materials and methods. The single centre study involved women aged 18 to 65 years. The surveyed 161 women were divided into three groups: 1st group 52 young women from 18 to 30 years old; 2nd group 54 women from 31 years old to the onset of menopause; 3rd group 55 postmenopausal women. The 1 and 2nd groups included women with preserved reproductive function. All women underwent a questionnaire survey, clinical examination, determination of anthropometric data, measurement of cfPWV, determination of arterial stiffness by volume sphygmography, 24-hour blood pressure monitoring with assessment of aortic stiffness and characteristics of the central pulse wave. Results. In group 1, the early age of menarche was associated with an increase in the rate of morning rise in SBP (r=-0.46, p=0.002) and a decrease in SEVR (r=0.33, p=0.03); the use of combined oral contraceptives correlates with an increase in the Weissler coefficient PEP/ET (R=0.3, p=0.03) and amplification of pulse pressure PPA (R=0.29, p=0.04). A history of 1 or 2 pregnancies is associated with a decrease in arterial stiffness. At the same time, 3 or more pregnancies in the anamnesis create the prerequisites for the formation of arterial stiffness. The early onset of pregnancy pathologies, namely, starting from the 1st or 2nd trimester of pregnancy, is associated with a violation of the characteristics of the reflected wave at a young age and the formation of arterial stiffness in the menopausal period. History of abortions was associated with PWVao (R=0.45, p=0.002), ASI (R=0.43, p=0.002) in group 2. History of miscarriages is associated with SEVR (R=0.52, p=0.00005) and SEVR to HR75 (R=0.27, p=0.04) in the menopausal period. Conclusion. Pathology of pregnancy, three or more pregnancies in history, early age of menarche, taking combined oral contraceptives, abortions and miscarriages in history are associated with an increase in arterial stiffness in the future, which predisposes women to the development of CVD and should be taken into account for preventive purposes.